Z Plasty Single Center Results in The Treatment of Pilonidal Sinus Disease in Children: Z Plasty Results in the Treatment of Pilonidal Sinus Disease - Yusuf Atakan Baltrak; Seniha Esin Sogut; Onursal Varlikli (Tropical Health and Medical Research, 2020)
Pilonidal sinus is a common chronic disease of the sacrococcygeal region. Treatment varies according to the clinical presentation of the disease. Although many surgical methods have proposed, the ideal approach is still lacking due to high recurrence rates. This study aimed to evaluate the role of Z-plasty in achieving primary recovery in pilonidal disease and morbidity and recurrence. Twenty-four patients (15 males and nine females) who underwent sinus excision and Z-plasty closure for the sacrococcygeal pilonidal sinus included in this study. Follow-up ranged from 6 to 12 months. There were 15 males and nine females with a median age of 16 years. The mean hospital stay was two days. There was no recurrence, and all patients were satisfied with the cosmetics. Two patients (5%) had numbness on the flap. No flap necrosis observed in any patient. Only three patients had a wound infection (7.5%). Wound seroma developed in five patients (12.5%). Although some technical expertise is required, excision of sinus and Z-plasty provides superior results in terms of recurrence and hospitalization of pilonidal sinus patients during hospitalization.